Analisis Body Positivity Movement Tentang Wanita Plus Size di Indonesia Melalui Tiktok - Suka, Irene Claudia Br Ginting; Fachruddin, Clarisa Fitria Salsabila; Wempi, J.A. (Jurnal Komunikasi Profesional, 2024)
The enforcement of beauty standards has caused anxiety for plus size women because it can lead to bullying. In reality, bullying still appears in social media activities and is even considered normal by most people without thinking about the impact on plus size women. Seeing this phenomenon, there is a need for a body positivity movement. The body positivity movement can promote self-love and acceptance of bodies of all shapes, sizes, or appearances. The presence of plus size content creators who raise their voices about body positivity has encouraged the emergence of a digital opinion movement from the public regarding this issue, thereby helping the success of the body positivity movement on TikTok. This research aims to understand the phenomenon of the body positivity movement regarding plus size women that occurs through TikTok in Indonesia. By using an interpretive paradigm through qualitative phenomenological methods, primary data collection was obtained through interviews and focus group discussions. This research uses the theory of digital movement, opinion and new media. The results of this research found that the body positivity movement on TikTok was carried out by contentcreatorplus size by creating content that had persuasive and motivational elements. The dominant character of new media is the character of interactivity which forms two-way and even multi-way communication, thereby encouraging a digital movement of opinions regarding body positivity for plus size women on TikTok.